Job satisfaction at the Sabah Youth and Sport (Federal) Department / Fatimah Abd Rahman - Abd Rahman, Fatimah (2011)
This study surveyed the job satisfaction at the Sabah Youth and Sport (Federal) Department, Kota Kinabalu. It aimed to determine the level of job satisfaction at the Sabah Youth and Sport (Federal) Department and it identified possible ways to increased and improved the job satisfaction at the Youth and Sport (Federal) Department. The respondents were 40 staff and officers from Management and Professional (Grade S41-S52), Support Group 1 (Grade N17-N26, Grade S17-S38) and Support Group 2 (Grade N16 and below). Data was collected by questionnaire and some interview to respondents. The questionnaire had asked about level of satisfaction with variable factors that associated to job satisfaction at the Sabah Youth and Sport (Federal) Department. Findings showed that staff and officer were satisfied with their job. All independent variables such as compensation, opportunities for growth, workplace environment and resources, teamwork, leadership and policy does not given any differences toward respondents in three group of post category and it is significantly associated with job satisfaction among staff and officer at the Sabah Youth and Sport (Federal) Department.